A Dynamic Motion Tracking Control Approach for a Quadrotor Aerial Mechanical System - Hugo Yañez-Badillo; Francisco Beltran-Carbajal; Ruben Tapia-Olvera; Antonio Valderrabano-Gonzalez; Antonio Favela-Contreras; Julio C. Rosas-Caro (Shock and Vibration)
This paper deals with the reference trajectory tracking problem and simultaneous active disturbance suppression on a class of controlled aerial mechanical systems by processing measurable output signals. A novel dynamic control method for desired motion reference trajectory tracking for quadrotor helicopters is introduced. Measurements of position output signals for efficient and robust tracking of motion profiles specified for the unmanned aerial vehicle are only required. Thus, differentiation of signals and real-time estimation of disturbances affecting the multi-input multioutput, underactuated nonlinear dynamic system are unnecessary. The presented active control approach can be directly extended for a class of vibrating mechanical systems. Analytical, experimental, and numerical results are presented to prove the satisfactory performance of the proposed trajectory tracking control approach for considerably perturbed operating scenarios.